Determinants of user satisfaction in internet use among socio-economically advantaged and disadvantaged groups: The role of digital access and government policy - Younghoon Chang; Siew Fan Wong; Myeong-cheol Park (International Telecommunications Society (ITS), 2014)
Digital divide is one of the most concerning issues today. It positions those who 'have-no' access to technology at disadvantage socially and economically. The key to reduce digital divide is to provide access to basic technology and information content. This study explored the role of government policy support in affecting digital access which in turns determining user satisfaction toward Internet use. A large data set that was provided by the Korea Information Society Development Institute confirmed the existence of digital divide in South Korea along the line of education and income. The proposed research model was tested using survey data of 233 socio-economically advantaged (SEA) individuals and 319 socioeconomically disadvantaged (SED) individuals. All hypotheses were supported with the exception of the relationship between policy support and social access for the SEA group. The study has implications on how governments should devise policies to facilitate technology and social access for different socio-economic groups within the country.
Keywords: 330; Digital Divide; Digital Access; Government Policy; Socio-Economically Disadvantaged; Socio-Economically Advantaged